Oxidative potential of PM2.5 during Atlanta rush hour: Measurements of in-vehicle dithiothreitol (DTT) activity. (September 2017) - Vreeland, Heidi; Weber, Rodney; Bergin, Michael; Greenwald, Roby; Golan, Rachel; Russell, Armistead G.; Verma, Vishal; Sarnat, Jeremy A.
Abstract: Although exposure to traffic emissions is frequently associated with negative health impacts, few studies have measured air pollution directly in-vehicle, and limited measurements of daily commuter exposure exist. This research, part of the Atlanta Commuter Exposures (ACE) Study, assesses on-roadway in-cabin particulate pollution (PM2.5 ) collected from scripted rush hour commutes on highways and on non-highway side streets. Water-soluble extracts from PM2.5 filters were analyzed for oxidative potential of water-soluble species using the dithiothreitol (DTT) assay, and results suggest that there may be substantial gas-phase DTT activity in fresh emissions. We measured DTTv activities (i.e., DTT activity normalized to the sampled air volume) that were on average two times higher than comparable measurements collected by stationary roadside monitoring sites. Although some of this difference may be attributable to positive artifacts due to relatively brief (2-h) quartz filter sampling durations, the current findings provide some indication that commuters encounter notably higher exposure to redox-active PM2.5 in the on-road environment. Strong correlations are observed between water-soluble DTT activity and water-soluble organic carbon (WSOC), specifically for the 'semivolatile' WSOC component (measured as the difference between denuded and non-denuded filters). Although potential for artifacts when measuring DTT activity of fresh emissions using filter-based methods is considerable, these results suggest that semivolatile organic species are important contributors to DTT activity, at least in environments where ambient PM2.5 is dominated by vehicular sources. Graphical abstract: Highlights: In-vehicle PM2.5 samples were collected during rush hour traffic in Atlanta, GA. Semivolatiles make important contributions to DTT activity in on-road environments. Compared to roadside monitors, PM collected in-vehicle may be more DTT-active.